Kiai's Democratic Leadership At Islamic Boarding School - muhamad baedowi; Muhamad Riza Chamadi (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aims to describe how the leadership management of al-Kamal Tambaksari Islamic boarding school, Kuwarasan, Kebumen. The research method that the author uses in this study uses the process of observation, documentation, and interviews within the framework of qualitative descriptive research. The results showed that leadership management in the al-Kamal Islamic boarding school runs according to the existing frame of reference in the management standards of the Islamic boarding school. Kyai runs the organization of Islamic boarding schools in a democratic and deliberation way.